The mechanical characteristics of the alloyed steel grades, used for continuous slugs casting at high temperatures - Ju. A. Samojlovich; V. I. Timoshpolski; I. A. Trusova; V. A. Matochkin; N. L. Mandel (Литьë и металлургия)
There are presented and analyzed the data on determination of mechanical characteristics (solidity and plasticity) taking into account their dependence on temperature for alloyed steel grades for the purpose of further use for calculations of thermostressed condition.